2020
DOI: 10.1108/sasbe-01-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Studying green consumer behavior through multiple lenses in a developing country

Abstract: PurposeThe study aims to explore the parameters that affect the purchase behavior of green consumers.Design/methodology/approachA mixed methodology concurrent study was adopted involving questionnaire-based empirical study along with a qualitative study to capture the lived experiences of the respondents. Inferences were drawn to understand green consumer behavior in a holistic way.FindingsWhile conducting in-depth interviews, many recurring themes emerged, such as environmentally friendly, health-conscious, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…People living in rural communities are mostly affected due to lack of grid connection and limited access to other energy options (Nwokocha et al , 2018). Small-scale business suffers setback; as a result, the rate of unemployment is rising significantly, economic opportunities in local communities are disappearing and resources that contribute to the economic development remain unidentified (Emodi and Boo, 2015; Gandhi, 2020). In total, 60% (15 of the 25) interviewees stated that there is lack of awareness of the benefits of solar energy in the medium to long term.…”
Section: Barriers For Solar Energy Implementation In Nigeriamentioning
confidence: 99%
“…People living in rural communities are mostly affected due to lack of grid connection and limited access to other energy options (Nwokocha et al , 2018). Small-scale business suffers setback; as a result, the rate of unemployment is rising significantly, economic opportunities in local communities are disappearing and resources that contribute to the economic development remain unidentified (Emodi and Boo, 2015; Gandhi, 2020). In total, 60% (15 of the 25) interviewees stated that there is lack of awareness of the benefits of solar energy in the medium to long term.…”
Section: Barriers For Solar Energy Implementation In Nigeriamentioning
confidence: 99%
“…That is why, according to the same author, products such as organics, natural personal care and pet care, and energy‐efficient products are achieving high volumes of sales. In India, some people behave greenly because of prestigious reasons (Gandhi, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Companies have to show how their pretenses are true in order to gain consumers' trust (Gandhi, 2021). Chen and Chang (2013) have recommended that companies should provide credible information, otherwise it will be difficult for marketers to persuade their consumers to buy their green products.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have consistently found that altruism plays a vital role in motivating consumers to adopt green products (Birch et al, 2018;Panda et al, 2020) and engage in environmentally-conscious behaviors (Gandhi, 2020;He et al, 2020;Pop et al, 2020;Tiwari, 2022). Studies have shown that individuals who exhibit stronger altruistic tendencies are more likely to make sustainable choices, such as purchasing eco-friendly products (Huh, 2011; Yulianti, F., Zulfikar, R., Lamsah.…”
Section: Introductionmentioning
confidence: 99%